Inequality, Leverage and Crises : The Case of Endogenous Default - Kumhof, Michael (IMF Working Papers; Working Paper ;, 2013)
The paper studies how high household leverage and crises can arise as a result of changes in the income distribution. Empirically, the periods 1920-1929 and 1983-2008 both exhibited a large increase in the income share of high-income households, a large increase in debt leverage of the remainder, and an eventual financial and real crisis. The paper presents a theoretical model where higher leverage and crises arise endogenously in response to a growing income share of high-income households. The model matches the profiles of the income distribution, the debt-to-income ratio and crisis risk for the three decades prior to the Great Recession.